Physical Characteristics of Flakes with Variations Kepok Banana Bud (Musa paradisiaca Linn.) and Mocaf Flour - Rahmadhia, Safinta Nurindra; Toni, Denna Rianda; Fitriani, Aprilia (PERTETA, 2024)
Yellow Kepok banana buds (KBB) are well-known for their high dietary fiber content and prospective use as functional food additives. High fiber consumption has been linked to diabetes prevention. The production of flakes derived from KBB has the potential to facilitate individuals in incorporating high-fiber food items into their daily diets. Nevertheless, the utilization of just Yellow KBB flour yields flakes that are deemed undesirable by consumers due to their firm consistency and deep hue. The substitution of Yellow KBB flour with a combination of wheat flour and mocaf has the potential to enhance the physical characteristics of the resulting flakes. The objective of this study is to assess the physical attributes of flakes derived from KBB. This particular flake was produced using a series of five distinct formulations. The present study employed a completely randomized design (CRD) with three replications. The formulas consist the proportions of wheat flour (WF), mocaf flour (MF), and Yellow Kepok banana bud (KBB). The following are the five ratios: (100%:0%:0%), (50%:50%:0%), (50%:37.5%:12.5%), (50%:25%:25%), and (50%:37.5%:12.5%). The water absorption, swelling ability, texture, and color of flakes produced from wheat, mocaf, and KBB flour were examined. The F2 sample, consisting of a composition of 50% wheat flour, 37.5% mocaf flour, and 12.5% yellow KBB flour, exhibited the highest water absorption value (63.19%) among all the samples. In addition to this, F2 can be characterized as a specimen exhibiting a relatively low level of hardness (1.63 N) and a correspondingly low fracture value (2.08 N). The F2 flakes had a much higher brightness value (37.06) in comparison to the other samples used yellow KBB flour.